Boundedness of Solutions for a Class of Second-Order Periodic Systems. (12th December 2013) - Jiang, Shunjun; Ding, Yan
Abstract : In this paper we study the following second-order periodic system: x ′′ + V ′ ( x ) + p ( x, t ) = 0, where V ( x ) has a singularity. Under some assumptions on the V ( x ) and p ( x, t ) by Ortega' small twist theorem, we obtain the existence of quasi-periodic solutions and boundedness of all the solutions.